Origin of the Fracture Strength Variation in Silicon Nitride Ceramics - Hiroya Abe; Tadashi Horta; Makio Naito; Nobuhiro Shinihara; Masataro Okumiya; Keizo Uematsu (The Minerals, Metals and Materials Society, 2000)
"A significant variation of strength was noted in silicon nitride ceramics made through the powder compaction processing with minor processing changes. The relevance of the fracture strength to the microstructure was examined in these ceramics. In the examination of microstructure, the ceramics were made into thinned specimens, and their internal structures were observed with an optical microscope in the transmission mode. This technique can distinguish a difference in microstructure associated with the minor processing changes. The strength of all ceramics examined in this experiment was qualitatively correlated with the -pore size distribution in the specimens. Clearly, the elimination of these detrimental defects will enhance the reliability of ceramics.IntroductionIn ceramics made through powder processing, a variation of properties is often encountered [l ,2]. This brings a major problem on producing reliable and cost-effective ceramics. The variation is often ascribed to the changes in the characteristics of defects. However, there is no clear evidence f\)r this explanation due to the lack of an adequate tool for identifying the defects determining the properties. Details of the origin of the variation have still been poorly understood.A new technique is very promising for clarifying the origin of the variation [3,4]. This has very high potential in detecting minor differences in structure for .engineering ceramics. With this technique, ceramics are made transparent with its thinning down to about 50 µ m and their internal structures are observed with various types of optical microscopes in the transmission mode. The characteristics of the defects determined through this approach were found to be directly related to the strength of the ceramics [4-6].The objective of this study is to clarify the ongm of fracture strength of silicon nitride ceramics. This material is representative of high performance ceramics, and the origin is of great practical interest. For this study, silicon nitride ceramics with minor changes in processing condition were prepared. Specific feature focused in this study is the difference of large pore structure determined with the new technique and its relevance to the strength of the silicon nitride ceramics."